2021
DOI: 10.1108/ijlss-11-2020-0183
|View full text |Cite
|
Sign up to set email alerts
|

An integrated spherical fuzzy AHP multi-criteria method for Covid-19 crisis management in regarding lean six sigma

Abstract: Purpose The Covid-19 pandemic has caused disruptions in many businesses. A difficult process has been experienced for businesses caught unprepared for this situation. The purpose of the study, the difficulties experienced in the business have been mapped in terms of crisis management. Design/methodology/approach For this purpose, crisis management strategies have been discussed in terms of lean six sigma (LSS) strategies. Afterward, LSS strategies have been weighted with the spherical fuzzy analytical hierar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Studies pertaining to the COVID-19 pandemic have also seen the use of F-AHP. Studies include analysing social isolation barriers (Upadhyay et al, 2021), COVID-19 crisis management (Demir & Turan, 2021), inhibitors to supply chain management (Biswas & Das, 2020) and evaluation of the quality of public transportation (Alkharabsheh & Duleba, 2021). However, a review of the extant literature indicated that F-AHP has not been used to evaluate the inhibitors to SCR post-COVID-19, especially in the context of the Indian pharmaceutical supply chain, and the current study tries to bridge this research gap.…”
Section: Theoretical Foundation Of the Concepts And Previous Studiesmentioning
confidence: 99%
“…Studies pertaining to the COVID-19 pandemic have also seen the use of F-AHP. Studies include analysing social isolation barriers (Upadhyay et al, 2021), COVID-19 crisis management (Demir & Turan, 2021), inhibitors to supply chain management (Biswas & Das, 2020) and evaluation of the quality of public transportation (Alkharabsheh & Duleba, 2021). However, a review of the extant literature indicated that F-AHP has not been used to evaluate the inhibitors to SCR post-COVID-19, especially in the context of the Indian pharmaceutical supply chain, and the current study tries to bridge this research gap.…”
Section: Theoretical Foundation Of the Concepts And Previous Studiesmentioning
confidence: 99%
“…The literature highlights the importance of these two techniques for continuous improvement programs (Doshi and Desai, 2017;Kaur et al, 2013;Kumar Sharma and Gopal Sharma, 2014). TPM is a component of the Lean methodology that managers of productivity improvement programs should be familiar with (Demir and Turan, 2021;Puram and Gurumurthy, 2021), whereas FMEA plays a vital role in preventive action (Tavana et al, 2021).…”
Section: Techniques Taught In Lssbb Certifications In Brazilmentioning
confidence: 99%
“…The COVID-19 pandemic has indeed caused disruptions to many businesses that are caught unprepared for this situation. To deal with this catastrophe, Demir and Turan (2021) propose a method to manage the COVID-19 pandemic crises, incorporating Lean Six Sigma strategies that have been weighted with the spherical fuzzy analytic hierarchy process, allowing a multi-criteria decision-making process to be implemented in a more effective and efficient manner.…”
Section: How Does Lean Six Sigma Improve Organisational Resilience Post the Covid-19 Pandemic?mentioning
confidence: 99%